Nanoliposomal vaccine containing long multi-epitope peptide E75-AE36 pulsed PADRE-induced effective immune response in mice TUBO model of breast cancer. (April 2020) - Zamani, Parvin; Teymouri, Manouchehr; Nikpoor, Amin Reza; Navashenaq, Jamshid Gholizadeh; Gholizadeh, Zahra; Darban, Shahrzad Amiri; Jaafari, Mahmoud Reza
Abstract: The main goal of peptide-based cancer vaccines is to induce the immune system and activation of effective T cell responses against cancerous cells. Nevertheless, the potency of peptide vaccines is insufficient in most of cases and had limited clinical success. Therefore, the optimization of peptide-based cancer vaccine is essential to achieve powerful therapeutic outcomes. One strategy to enhanced potency of peptide vaccines and induce strong immune responses is the preparation of multi-epitope peptide formulation containing both Th- and cytotoxic T lymphocyte–induced responses epitope using suitable delivery system. For this reason, we studied the effect of Dioleoylphosphatidylethanolamine-containing liposomal vaccine composed of a mixture of short peptides AE36 and E75 (HER2/neu-derived peptides) and long multi-epitope peptide E75-AE36 (linkage of short peptides) in combination with a Pan HLA-DR epitope (PADRE) peptide. These formulations were examined using a series of subcutaneously injection to HER-2 + TUBO-tumoured mice in prophylactic and therapeutic model. We observed that mice vaccinated with liposomal long peptide in combination with PADRE resulted in the superior induction of CD4 + and CD8 + T cells responses and significantly enhanced production of IFN-γ compared with liposomal short peptides and non-liposomal peptides formulations. Moreover, liposome-long peptide with PADRE led to the considerable reduction of tumour growth and lifespan induction in mouse model. In conclusion, our study indicated that liposomal formulation containing long multi-epitope peptide E75-AE36 with PADRE could be used as an effective multi-epitope prophylactic/therapeutic vaccine to generate potent antigen-specific CD8 + T-cell immune response and may be introduced as a possible candidate peptide vaccine for breast cancer. Graphical abstract: Image 1 Highlights: Long peptide induced effective immune response in mice TUBO model of breast cancer. Addition of PADRE led to an improvement of immunogenic peptide based cancer vaccines. Liposomal formulation containing antigenic peptides significantly induced stronger CD8 + T cell immune responses.